2004
DOI: 10.1080/14017430310016658
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term changes in pulmonary function and respiratory movements after cardiac surgery via median sternotomy

Abstract: The breathing pattern before sternotomy is predominantly abdominal but moves to a thoracic and upper thoracic pattern postoperatively and is associated with reduced pulmonary function. Therapeutic interventions aimed at correcting the less effective upper thoracic breathing pattern should likely be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 14 publications
3
53
0
13
Order By: Relevance
“…Sternotomy principally modifies the compliance of the rib cage, which reduces its mobility by more than 80% for up to 7 days after the surgery. This leads to atelectasis, reducing the DynC [8]. CPB may be responsible for changes in the StaC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sternotomy principally modifies the compliance of the rib cage, which reduces its mobility by more than 80% for up to 7 days after the surgery. This leads to atelectasis, reducing the DynC [8]. CPB may be responsible for changes in the StaC.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of PPCs may also be linked to factors related to anesthesia, such as the type and the time of anesthesia and the agent used [1,7], as well as to surgical factors related to the site of the incision, surgical type and intra-operative mechanical ventilation [1,7,8]. In heart surgeries there may be a necessity to employ cardiopulmonary bypass (CPB); responsible for the development of systemic and pulmonary inflammatory responses with the latter leading to mechanical respiratory dysfunction [9].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our results, these authors concluded that FVC and PEF, among other parameters that were analyzed, were significantly reduced after surgery, and, although the exhibited discrete increases over time, were still affected an average of 3.5 months after surgery. Similarly, a further two studies also assessed FVC after heart surgery, concluding that FVC was significantly reduced until POD 7 23 and 8, 20 when compared with preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have also demonstrated varying degrees of pulmonary dysfunction over the short term after heart surgery, although the age groups involved were different. 23,24 * p < 0.01 FVC = forced vital capacity; POD = postoperative day. On the first day after surgery a sudden and significant drop in mean VE was observed and this was maintained until postoperative day three.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation